The Effect of Music Therapy on Anxiety in Pre-Anesthesia in the Operation Room of Genteng Hospital Banyuwangi - Katmini; Suryanto (Journal of Nursing Practice, 2022)
Background: Pre-anesthesia preparation is very important to minimize risks during surgery. This is because the outcome of surgery depends on the assessment of the patient's condition and the preoperative preparation performed on the pre-anesthetized patient. Music has many benefits for human health and can provide good mental strength for listeners.